Autonomous Learning by Utilizing Learning Resources of the Onleihe Goethe Digital Library, UM PSPBJ Student Institute Class of 2018 and 2020 - Dhea Elvira Ressa Putri (Universitas Negeri Malang, 2021)
The purpose of this study was to describe the usefulness of learning resources contained in the Onleihe Goethe Institute digital library and student responses to the use of learning resources in it for autonomous learning. The data sources for this study were 20 German language students class 2018 who were at the linguistic level equivalent to B1 GER and 26 German language students batch 2020 who were at the level equivalent to A2 GER. Data was obtained from closed questionnaires and interviews. Furthermore, the data was analyzed using spiral data analysis. The results of the study indicate that the limited ability of the German language skills of 2020 students is an obstacle to utilizing the learning resources contained in the Onleihe Goethe Institute digital library. On the other hand, the limited German language skills of the 2018 students are a motivation to make the most of the learning resources contained in the Onleihe Goethe Institute digital library.